The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1939-165x.2008.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphologic differentiation of benign and malignant mammary tumors in fine needle aspirate specimens from irradiated female Sprague–Dawley rats

Abstract: FNA is an accurate method for differentiating benign and malignant rat mammary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Our results demonstrated useful and reliable criteria in differentiating benign from malignant mammary tumors, such as cell dissociation, nuclear size, cell uniformity, nucleoli, nuclear margin, chromatin pattern, cellularity, presence of necrotic debris, inflammation, and RBC. This finding was in line with previous published studies in veterinary and human medicine [ 8 , 21 , 22 , 25 ]. In contrast, Yildirim and Gurel [ 25 ] demonstrated that inflammatory cells, including macrophages and necrotic debris, were not distinctive in making a differentiation between benign and malignant CMTs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrated useful and reliable criteria in differentiating benign from malignant mammary tumors, such as cell dissociation, nuclear size, cell uniformity, nucleoli, nuclear margin, chromatin pattern, cellularity, presence of necrotic debris, inflammation, and RBC. This finding was in line with previous published studies in veterinary and human medicine [ 8 , 21 , 22 , 25 ]. In contrast, Yildirim and Gurel [ 25 ] demonstrated that inflammatory cells, including macrophages and necrotic debris, were not distinctive in making a differentiation between benign and malignant CMTs.…”
Section: Discussionsupporting
confidence: 93%
“…The results concerning the presence of ECM corroborate the findings of other authors and support the opinion that the cytological diagnosis of complex/mixed tumors is more challenging and difficult [ 6 , 21 , 37 ]. However, some studies have reported that the mucosecretory material was much more frequent in the malignant compared to the benign mammary tumors [ 6 , 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Most false positive results were related to the presence of atypical single epithelial cells in fibroadenomas, and some false negative were solid carcinomas by histologic examination. The low cellularity and clean background led to misdiagnosis of the solid carcinomas as benign rather than malignant [52]. In addition, care must be taken when squamous cells are seen on FNA, while a broad differential diagnosis should be considered [58].…”
Section: Sensitivity and False Positive Or Negative Resultsmentioning
confidence: 99%
“…Fine needle aspiration cytology (FNAC) of the breast is becoming an increasingly important diagnostic tool in the assessment of breast malignancies and their further subtyping with a high degree of accuracy [50,51]. It has been shown to be rapid, minimally invasive and safe diagnostic procedure in pregnancy and lactation, indicating suspicious or malignant findings in 95% of lesions [48,[50][51][52]. ThinPrep Papanicolaou test is considered to be a trusted and widely used technique, much easier and faster as procedure.…”
Section: Fine Needle Aspirationmentioning
confidence: 99%
“…Grades of malignancy determined using the Kiel classification and the working formulation have been found to be prognostic factors for time to relapse and survival time . Our rubric was developed based partly on the Kiel classification and also on other published cytology scoring rubrics that have been used in studies on human hepatocellular carcinoma and mammary tumors of rats . To our knowledge, our study is the 1 st to use a scoring rubric to evaluate cytologic samples of canine lymphoma at diagnosis and at relapse.…”
Section: Discussionmentioning
confidence: 99%